Collective empowerment through information and communication technologies: co-creation processes in underserved communities in Cape Town - Lorini, Maria Rosa (Department of Information Systems, 2019)
This research investigates the potential of Information and Communication Technology (ICT) to provide opportunities for groups of people to improve their lives and their communities. Further, the study explores innovative methodological approaches which could be conducive for collective empowerment. Grounded in current ICT4D research, the thesis tries to resolve the gap related to how to include collective approaches and participation in design. The study is framed by critical social theory and the capability approach but with special attention to collective and relational dimensions of agency, capabilities and empowerment. The analysis is based on three digital co-creation case studies which unfolded over a four-year project in underserved settlements in Cape Town, South Africa. The study employed a qualitative methodological approach and followed abductive logic. The research evolved through cycles of ethnographic studies; co-design; and theoretical phases. Each cycle built on the previous one in theory and practice. The initial inductive approach employed open coding followed by content analysis to reflect on the discourses and meanings of ICTs originating from the focus groups in the communities. In the design phase, three case studies were analysed using strategies suitable for research involving cultural differences between researcher and participants. The processes were further evaluated during their development from the theoretical lenses of participatory design, frugal innovation and social capital theory. Five papers provide an analysis of the research project highlighting its evolution, from the creation of digital storytelling until the development of social businesses, and discussing how social relations and group actions determine uses of ICTs and encourage collective ways for information access, information production, creativity development and networking. These concepts supported the analysis of the findings to deepen the use of the theories and to develop a process model for ICT4D projects. The outcome of the research are four propositions and three principles for a sensible emergent approach for ICT4D projects. Their chances of success and sustainability increase if based on grassroots, collective, socially engaged co-creation initiatives. Theoretically, the process model has the potential to improve our understanding and support our way of operating to make ICT4D initiatives more inclusive, more empowering to participants, including the researchers, and to become oriented towards community development and people’s emancipation.